IMPLEMENTASI REWARD PADA PRAKTEK PEMBELAJARAN PAI DI TPA NURUL YAQIN DESA BANYU HIRANG KECAMATAN AMUNTAI SELATAN - Susanti, Ria; Azmi, Falhi; Maulana, M Aditya; Noorfadillah, Muhammad; Amalia, Fitria; Isabella, Isabella (FIKRUNA Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2022)
One method and learning strategy that is often used and very effective in stimulating and fostering enthusiasm and motivation for learning is giving rewards. Reward in the world of education and Islam means tsawab/pahala/reward. Rewards are the result of good deeds given by God. And the word "tsawab" in relation to Islamic education is giving good rewards for the good behavior of students. This study aims to describe how the implementation of Islamic Education Learning uses the reward method at TPA (Al-Qur'an Education institutions) Nurul Yaqin Banyu Hirang Amuntai Selatan by students from STAI Rakha Amuntai. By using a type of field research (field research) that is descriptive, and with a qualitative approach.. The results of the study show that giving rewards in Islamic education learning at TPA Nurul Yaqin by STAI Rakha Amuntai students as a whole ran smoothly and was effective in increasing the motivation and enthusiasm of the students to pay attention to learning. There are three types of rewards given by students in the Islamic education learning process at TPA Nurul Yaqin, namely the first social reward (reinforser) such as words of praise "smart kid/great kid" this form is also called verbal reward, second reward ( reinforser) activities such as giving applause and yells, and the third reward (reinforser) is symbolic such as giving material gifts. Supporting factors in the form of higher student motivation, while the obstacle is limited funds. One solution is to use rewards other than material forms if there are funding constraints, pay special attention to students, and provide special guidance to students.